Microcephaly-chorioretinopathy syndrome, autosomal recessive form: a case report - Rosa, Rafael Fabiano Machado; Enk, Flávia; Camargo, Korine; Travi, Giovanni Marco; Freitas, André; Rosa, Rosana Cardoso Manique; Graziadio, Carla; Mattos, Vinicius Freitas de; Zen, Paulo Ricardo Gazzola (São Paulo Medical Journal, 2015)
CONTEXT: The autosomal recessive form of microcephaly-chorioretinopathy syndrome is a rare genetic condition that is considered to be an important differential diagnosis with congenital toxoplasmosis. CASE REPORT: Our patient was a seven-year-old white boy who was initially diagnosed with congeni-tal toxoplasmosis. However, his serological tests for congenital infections, including toxoplasmosis, were negative. He was the first child of young, healthy and consanguineous parents (fourth-degree relatives). The parents had normal head circumferences and intelligence. The patient presented microcephaly and specific abnormalities of the retina, with multiple diffuse oval areas of pigmentation and patches of cho-rioretinal atrophy associated with diffuse pigmentation of the fundus. Ophthalmological evaluations on the parents were normal. A computed tomography scan of the child’s head showed slight dilation of lateral ventricles and basal cisterns without evidence of calcifications. We did not find any lymphedema in his hands and feet. He had postnatal growth retardation, severe mental retardation and cerebral palsy. CONCLUSIONS: The finding of chorioretinal lesions in a child with microcephaly should raise suspicions of the autosomal recessive form of microcephaly-chorioretinopathy syndrome, especially in cases with an atypical pattern of eye fundus and consanguinity. A specific diagnosis is essential for an appropriate clini-cal evaluation and for genetic counseling for the patients and their families.